Simvastatin Suppresses Interleukin Iβ Release in Human Peripheral Blood Mononuclear Cells Stimulated With Cholesterol Crystals. (November 2018) - Boland, Anna J.; Gangadharan, Nisha; Kavanagh, Pierce; Hemeryck, Linda; Kieran, Jennifer; Barry, Michael; Walsh, Patrick T.; Lucitt, Margaret
Statins are mainstream therapy in the treatment and prevention of cardiovascular disease through inhibitory effects on cholesterol synthesis. However, statins' beneficial effects in cardiovascular disease may also be attributable to their role as anti-inflammatory mediators. Here, we investigated the effects of simvastatin treatment on expression levels of interleukin (IL) 1β in both patient with hyperlipidemia and healthy human peripheral blood mononuclear cells (PBMCs) using cholesterol crystals (CC), a cardiovascular pathogenic stimulus for activation of the NOD-like receptor pyrin domain–containing protein 3 (NLRP3) inflammasome. Cholesterol crystal-induced NLRP3 inflammasome activation was used to trigger maturation and release of IL-1β in PBMCs. Specifically, isolated PBMCs from patients with hyperlipidemia at baseline and following 8 weeks of in vivo treatment with simvastatin (10-20 mg) daily were stimulated with lipopolysaccharide (LPS; 100 ng/mL) for 3 hours to induce proIL-Iβ expression followed by CC (2 mg/mL) stimulation for further 18 hours to activate the NLRP3 inflammasome complex to induce maturation/activation of IL-1β. Peripheral blood mononuclear cells were also isolated from healthy donors and stimulated in vitro with simvastatin (50, 25, 5, and 2 µmol/L) prior to stimulation with LPS and CC as described above. The effects of simvastatin treatment on levels of IL-1β expression were determined by enzyme-linked immunosorbent assay and western blot. Both in vitro and in vivo treatments with simvastatin led to a significant reduction in the levels of expression of IL-1β in response to stimulation with CC. Simvastatin inhibits the expression and activation of IL-1β induced by CC in PBMCs, which may contribute to its protective role in patients with cardiovascular disease.